The Impact Of User’s Satisfaction Enablers On Net Benefits Of Human Resource Management Information System (Hrmis) In The Malaysian Public Organizations - Sappri, Mazlan Mohd (2017)
This study is motivated by the lack of knowledge in understanding users’ satisfaction among the employees of information system (IS) in Malaysian Public Organizations. In this regard, this study attempts to fill the knowledge gap by identifying the factors that contribute to the satisfaction of the Human Resource Management Information System (HRMIS). The HRMIS was selected based on deterioration of employees’ acceptance, especially in addressing the issues related to user satisfaction. In addition, the usage of HRMIS is a must in all government agencies in managing human resource. Therefore, based on the underlying IS models by DeLone and McLean, the study applied the following variables; system quality, information quality, technostress, service quality, user involvement and self-readiness to test the relationship between IS users’ satisfaction and net benefits.